Myelin abnormality in Charcot–Marie–Tooth type 4J recapitulates features of acquired demyelination. Issue 4 (30th March 2018) - Hu, Bo; McCollum, Megan; Ravi, Vignesh; Arpag, Sezgi; Moiseev, Daniel; Castoro, Ryan; Mobley, Bret; Burnette, Bryan; Siskind, Carly; Day, John; Yawn, Robin; Feely, Shawna; et al.
Abstract : Objective: Charcot–Marie–Tooth type 4J (CMT4J) is a rare autosomal recessive neuropathy caused by mutations in FIG4 that result in loss of FIG4 protein. This study investigates the natural history and mechanisms of segmental demyelination in CMT4J. Methods: Over the past 9 years, we have enrolled and studied a cohort of 12 CMT4J patients, including 6 novel FIG4 mutations. We evaluated these patients and related mouse models using morphological, electrophysiological, and biochemical approaches. Results: We found sensory motor demyelinating polyneuropathy consistently in all patients. This underlying myelin pathology was associated with nonuniform slowing of conduction velocities, conduction block, and temporal dispersion on nerve conduction studies, which resemble those features in acquired demyelinating peripheral nerve diseases. Segmental demyelination was also confirmed in mice without Fig4 ( Fig4 −/− ). The demyelination was associated with an increase of Schwann cell dedifferentiation and macrophages in spinal roots where nerve–blood barriers are weak. Schwann cell dedifferentiation was induced by the increasing intracellular Ca 2+ . Suppression of Ca 2+ level by a chelator reduced dedifferentiation and demyelination of Schwann cells in vitro and in vivo. Interestingly, cell‐specific knockout of Fig4 in mouse Schwann cells or neurons failed to cause segmental demyelination. Interpretation: Myelin change in CMT4J recapitulates the features of acquired demyelinating neuropathies. This pathology is not Schwann cell autonomous. Instead, it relates to systemic processes involving interactions of multiple cell types and abnormally elevated intracellular Ca 2+ . Injection of a Ca 2+ chelator into Fig4 −/− mice improved segmental demyelination, thereby providing a therapeutic strategy against demyelination. Ann Neurol 2018;83:756–770